Population dynamics and spatial distribution of the Calosoma granulatum Perty., 1830 (Coleoptera: Carabidae) in soybean/corn crop - Martins, Ivan Carlos Fernandes; Cividanes, Francisco Jorge [UNESP]; Barbosa, José Carlos [UNESP]; Junior, Joaquim Alves de Lima; da Silva, André Luiz Pereira [UNESP]; Campos, Lourival Dias; Haddad, Gianni Queiroz [UNESP]; da Silva, Anderson Gonçalves (Southern Cross Publishing, 2018)
The (Calosoma granulatum Perty., 1830) (Coleoptera: Carabidae) is an important predator of agricultural pests. The knowledge about the spatial and temporal behavior and influence of the environmental structure may be fundamental for the application of conservative biological control. This study evaluated whether phenology of cultivated plants and meteorological factors influencing the occurrence and spatial distribution of the predaceous beetle (Calosoma granulatum) in soybean/corn crop. Three hypotheses were tested: H1: that this predaceous beetle occurs naturally in aggregated spatial patterns; H2: its presence/absence in agricultural fields is influenced by meteorolical factors; and H3: the presence of the beetle bank in crop fields affects the carabid spatial distribution patterns. To test these hypotheses, we measured annual population fluctuations to examine the influence of meteorological factors, and to determinate the spatial distribution using dispersion indices and probabilistic models based on the Calosoma granulatum frequency distribution in one hectare of soybean/corn crop using multiple regression analysis (stepwise). The results showed that population peaks of the beetle in soybean crop were coincident with their reproductive period regardless of meteorological factors. The analyses of the spatial distributions showed that Calosoma granulatum has a clustered distribution, and the highest numbers were observed in soybean crop. These results support the hypothesis that the beetles have an aggregated pattern. However, the hypotheses that the occurrence and distribution of this predator is directly influenced by environmental distribution factors and by the presence of herbaceous refuge is not supported.
Keywords: Carabid beetles; Dispersion indexes; Glycine max; Linear interpolation; Natural pest control; Predator; Zea mays